MSMEs Productivity in Nigeria - Ajuwon, Oluseye Samuel; Ikhide, Sylvanus; Akotey, Joseph Oscar (European Journal of Economics and Business Studies, 2017)
This study uses the World bank enterprise survey data for Nigeria to examines Micro, Small and Medium Enterprises (MSMEs) productivity rate in the Nigerian economy. The study explores factors that constrain MSMES output growth in Nigeria. Some of the factors identified include huge infrastructural gap, inadequate institutional support and low access to credit. The resultant effect is a low investment commitment amongst MSMEs thus hampering the productivity of MSMEs in the Nigerian economy. The MSMEs productivity growth rate was measured using annual sales of firms from the World bank enterprise survey data for Nigeria. This research employs the non-parametric variance estimation using the locally-weighted scatterplot smoothing (LOWESS) method on three sets of two-points data (2006 and 2003, 2008 and 2002, and finally 2012 and 2009) of annual fiscal sales for each category of firms comprising micro, small, medium and large firms. The result shows that the small businesses have a negative productivity growth rate in Nigeria. This in line with IFC (2013) which found that small businesses have the least productivity growth rate amongst firms of all sizes. However, this study departs from IFC findings which states that small businesses’ low productivity growth rate is tenable across all the sectors of the economy. The study found that small businesses actually recorded high productivity growth rate in some subsectors of the economy that specializes in product customization such as garment and furniture. Therefore, this study validates the flexible specialization theory that emphases the economic importance of MSMEs in the post-industrial era where product customization is the new order of production. The policy implication of this study is that any targeted intervention in the MSMEs sub-sector of the economy designed to increase productivity, should be channeled into the subsector with the most employee specialization as well as product customization.Keyword(s): MSMEs, small business, Output, Productivity, JEL Classifications: P42 M13 O55